Recent Advances of Seed‐Mediated Growth of Metal Nanoparticles: from Growth to Applications - He, Meng‐Qi; Ai, Yongjian; Hu, Wanting; Guan, Liandi; Ding, Mingyu; Liang, Qionglin (Advanced materials (Weinheim), 2023)
Unprecedented advances in metal nanoparticle synthesis have paved the way for broad applications in sensing, imaging, catalysis, diagnosis, and therapy by tuning the optical properties, enhancing catalytic performance, and improving chemical and biological properties of metal nanoparticles. The central guiding concept for regulating the size and morphology of metal nanoparticles is identified as the precise manipulation of nucleation and subsequent growth, often known as seed‐mediated growth methods. However, since the growth process is sensitive not only to the metal seeds but also to capping agents, metal precursors, growth solution, growth/incubation time, reductants, and other influencing factors, the precise control of metal nanoparticle morphology is multifactorial. Further, multiple reaction parameters are entangled with each other, so it is necessary to clarify the mechanism by which each factor precisely regulates the morphology of metal nanoparticles. In this review, to exploit the generality and extendibility of metal nanoparticle synthesis, the mechanisms of growth influencing factors in seed‐mediated growth methods are systematically summarized. Second, a variety of critical properties and applications enabled by grown metal nanoparticles are focused upon. Finally, the current progress and offer insights on the challenges, opportunities, and future directions for the growth and applications of grown metal nanoparticles are reviewed. The state‐of‐the‐art development in seeded growth methods from key influencing factors of growth and applications of grown metal nanoparticles are summarized in this review to highlight the achievements and help researchers understand the current investigation status of seed‐mediated methods. Furthermore, the challenges faced by seed‐mediated methods are outlined and the future directions for advancing seed‐mediated methods are outlooked.